Cardiovascular risk in various medical specialities. The results of the Russian multi-centre scientific and educational programme “Russian Doctors’ Health” - Zh. D. Kobalava; Yu. V. Kotovskaya; S. A. Shalnova (Кардиоваскулярная терапия и профилактика, 2010)
Aim. To assess the risk of fatal cardiovascular (CVD) events in medical doctors of various specialities, using modern risk scales, and to identify the target groups for primary prevention with a fixed-dose combination of enalapril / hydrochlorothiazide (HCT) and simvastatin. Material and methods. The programme included 12 non-teaching Russian hospitals and was divided into epidemiological, educational, therapeutic, and control phases. In 699 doctors, aged >40 years and representing 43 specialities (22,8% men; mean age 50,5±11,7 years), the risk of fatal CVD events and coronary events was assessed with SCORE and Framingham scales, respectively. All doctors were informed about their individual risk and target levels of risk factors (RFs), and also taught to self-control their blood pressure, physical activity, and body mass. In total, 287 doctors participated in the therapeutic phase (6 months): 52 were included in the antihypertensive therapy (AHT) group (enalapril/HCT); 38 – in the simvastatin group; and 197 – in the combined therapy group (AHT and simvastatin). Six months after the end of the therapeutic phase, the prevalence of continuing pharmaceutical and non-pharmaceutical primary prevention was analysed. Results. The prevalence of the main RFs was high: dyslipidemia was observed in 69,2% of the participants, AH – in 55,6%, abdominal obesity – in 34,5%, and smoking – in 14%. As many as 54,5% of the doctors had at least 3 RFs, while 25,8% had high SCORE-assessed risk, and 47,1% had indications for pharmaceutical primary prevention. The most adverse RF profile was registered in surgeons. Pharmaceutical primary prevention with a fixed-dose combination of enalapril/HCT and/or simvastatin significantly reduced both SCORE and Framingham risk levels. Six months after the therapeutic phase, 30,2% of the doctors stopped the treatment, and 37,2% continued pharmaceutical primary prevention. Conclusion. The results of the programme point to the high prevalence of modifiable RFs in middle-aged medical doctors. The data obtained could be a basis for the programs of primary CVD prevention.